The influence of a preoperative information brochure on the experience of patients undergoing awake surgery in private hospitals - Martins, Johanna Elizabeth (My University, 2018)
Undergoing surgery without having general anaesthesia has become an option for many surgical patients. Awake patients are able to communicate with the surgical team which allows the surgical team to gain understanding of the patient’s experience. This is an important aspect of perioperative care and is in line with the theory of Human Becoming according to Parse, (2011). Literature suggests that patients who have received information preoperatively about their planned perioperative journey experience less anxiety and fear relating to their surgery. The purpose of this study was to explore the perioperative experiences and needs of patients undergoing awake surgery. A qualitative exploratory descriptive three step design of data collection was implemented for this study. In step one an integrative review identified patient experiences of the perioperative journey. The literature was critically analysed for relevance and inclusion. This information formed the basis for inclusion in step two. Step two explored the perioperative experience of participants who had undergone awake surgery by interviewing a group of participants using interviews and probe questions extracted from the literature. The information gleaned from the interviews was grouped for content similarity and was used to create an information pamphlet which informed participants about their perioperative journey. In step three the information pamphlet was handed to participants preoperatively and the same participants rated the usefulness of the information pamphlet postoperatively by answering a dichotomous question. Participants had the opportunity to add comments. The population for this study was all patients who were scheduled for ophthalmic, orthopaedic, urological or plastic, surgery using awake surgery in four large private hospitals in Gauteng and Mpumalanga. Patients younger than 18 years of age as well as those receiving sedation or general anaesthesia were excluded from the population. This study showed that participants had positive experiences of being awake during surgery. A number of participants found the experience of being awake during surgery interesting and enjoyed being able to ask questions and participate in dialogue. Participants rated the information pamphlet as useful. Two areas of concern was elicited, namely communication and nursing care within the operating theatre environment. The objectives for this study were met. Key words: perioperative journey, awake surgery, regional and local anaesthesia, nursing
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2018.
Keywords: Awake Surgery; Anesthesia; Perioperative Care